Long-term scenarios for reaching climate targets and energy security in UK. (September 2015) - Spataru, Catalina; Drummond, Paul; Zafeiratou, Eleni; Barrett, Mark
Abstract: The construction and subsequent analysis of scenarios using energy systems models is an essential tool in energy policy making. This paper presents two descriptive scenarios for the development of the UK energy system to 2050, using four subsequent decadal time-slices. The two scenarios, K_Scenario and Z_Scenario, were modelled with the use of the Department of Energy and Climate Change (DECC) 2050 Pathways Calculator. K_Scenario is a scenario in which the use fossil fuels with carbon capture and storage (CCS) are prominent in the power sector, while Z_Scenario focuses on the development of renewables with energy storage and nuclear power. Both scenarios seek to achieve the UK's legally binding target of an 80% reduction in GHG emissions from 1990 levels by 2050. Abatement is achieved through numerous developments in each of the scenarios, including the development and use of shale gas, hydrogen, additional wind and solar deployment, the expansion of bioenergy and use of carbon capture and storage (CCS). These developments must be driven by policies designed to pursue dramatic decarbonisation.